Strategi Penguatan Budaya Organisasi Untuk Meningkatkan Komitmen Guru di SDN Pasawahan 08 Dayeuhkolot dan SDN Jatisari Baleendah - Tutty Rokhayati Rosa, Ade; Anggraeni, Rishawarti; Muhaemin, Akhmad; Mardiana, Nina (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
Organizational culture is a fundamental element in creating a harmonious work environment and supporting the achievement of educational goals. This study aims to explore strategies for strengthening organizational culture implemented by school principals in an effort to improve teacher commitment at SDN Pasawahan 08 Dayeuhkolot and SDN Jatisari Baleendah. The method used is a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, observations, and documentation studies. The results of the study indicate that school principals play a central role in shaping organizational culture through exemplary leadership, effective communication, teacher involvement in decision-making, and the implementation of literacy, religious, and award programs. This strategy has an impact on increasing teachers' sense of belonging, motivation, and loyalty to the institution, which ultimately strengthens professional commitment. These findings emphasize the importance of participatory leadership and collective values ​​in building a strong organizational culture in elementary schools.